1995
DOI: 10.1111/j.1471-0528.1995.tb11433.x
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy, sleep quality and psychological wellbeing

Abstract: Objective To examine the effect of hormone replacement therapy upon sleep quality and duration in postmenopausal women. Design Randomised, single‐blind, placebo‐controlled trial. Setting Sleep research laboratory. Subjects Thirty‐three healthy postmenopausal women. Interventions Continuous 0–625 mg conjugated equine oestrogens with 0.15 mg cyclic norgestrel taken for 12 days per 28 day cycle. Main outcome measures Occurrence of vasomotor symptoms, polysomnographic sleep stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(25 citation statements)
references
References 16 publications
(21 reference statements)
2
22
1
Order By: Relevance
“…We did not detect any major alterations in polysomnographic recordings in either group, although studies have found that estrogen treatment led to significant relief of menopausal symptoms [19]. This discrepancy may be due to differences in study populations (eg, whether the women were perimenopausal or postmenopausal, had a natural or a surgically induced menopause, or were younger or older) and methods (eg, different dosage, form, and duration of the hormonal treatment).…”
Section: Discussioncontrasting
confidence: 74%
“…We did not detect any major alterations in polysomnographic recordings in either group, although studies have found that estrogen treatment led to significant relief of menopausal symptoms [19]. This discrepancy may be due to differences in study populations (eg, whether the women were perimenopausal or postmenopausal, had a natural or a surgically induced menopause, or were younger or older) and methods (eg, different dosage, form, and duration of the hormonal treatment).…”
Section: Discussioncontrasting
confidence: 74%
“…Two papers analyzing the effect of oral synthetic estrogen on objectively determined hot flashes and sleep found improvements [54,55, Class I]. In contrast, another study analyzing the combination of estrogen and progesterone [52] found no difference in objective hot flashes between treatment and placebo.…”
Section: Sleep Problems During Perimenopausementioning
confidence: 89%
“…However, in a study by Freedman and colleagues, no association between sleep quality and hot flushes was found when symptomatic postmenopausal women were compared with asymptomatic or premenopausal women 41 . From the six sleep studies with polysomnography and EPT administration, two did not report any vasomotor symptoms 9,37 and one investigated only asymptomatic women 15 , but two found a decrease in vasomotor symptoms 17,38 . After administering conjugated equine estrogen in combination with norgestrel or placebo for 12 weeks to 33 postmenopausal women (age range 49-60 years), Purdie and colleagues found no improvements in objective sleep, though vasomotor symptoms decreased and psychological well-being improved 38 .…”
Section: Discussionmentioning
confidence: 94%